The effects of simulated interruptions on mobile search tasks. (9th October 2021) - Hoeber, Orland; Harvey, Morgan; Dewan Sagar, Shaheed Ahmed; Pointon, Matthew
Abstract: While it is clear that using a mobile device can interrupt real‐world activities such as walking or driving, the effects of interruptions on mobile device use have been under‐studied. We are particularly interested in how the ambient distraction of walking while using a mobile device, combined with the occurrence of simulated interruptions of different levels of cognitive complexity, affect web search activities. We have established an experimental design to study how the degree of cognitive complexity of simulated interruptions influences both objective and subjective search task performance. In a controlled laboratory study (n = 27), quantitative and qualitative data were collected on mobile search performance, perceptions of the interruptions, and how participants reacted to the interruptions, using a custom mobile eye‐tracking app, a questionnaire, and observations. As expected, more cognitively complex interruptions resulted in increased overall task completion times and higher perceived impacts. Interestingly, the effect on the resumption lag or the actual search performance was not significant, showing the resiliency of people to resume their tasks after an interruption. Implications from this study enhance our understanding of how interruptions objectively and subjectively affect search task performance, motivating the need for providing explicit mobile search support to enable recovery from interruptions.